2018
DOI: 10.1002/bjs.10931
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival before and after centralization of gastric cancer surgery in the Netherlands

Abstract: Centralization of gastric cancer surgery was associated with reduced postoperative mortality and improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 37 publications
5
60
1
2
Order By: Relevance
“…Second, our study is limited in that longterm outcomes, such as recurrence-free survival and overall survival, were not evaluated. Most recent report from Netherland demonstrated that centralization of gastric cancer surgery was associated with improved both short and long-term outcome [33]. Interestingly, this report showed that survival improved not only for patients who underwent gastrectomy but also for all patients, irrespective of treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Second, our study is limited in that longterm outcomes, such as recurrence-free survival and overall survival, were not evaluated. Most recent report from Netherland demonstrated that centralization of gastric cancer surgery was associated with improved both short and long-term outcome [33]. Interestingly, this report showed that survival improved not only for patients who underwent gastrectomy but also for all patients, irrespective of treatment.…”
Section: Discussionmentioning
confidence: 90%
“…HER2 testing and the administration of trastuzumab in gastroesophageal cancer might be underexposed within individual centers, because gastroesophageal cancer has a relatively low incidence in Western countries, and only 15-25% of the adenocarcinomas show HER2 overexpression [14][15][16]. In recent years, several studies have been published showing that gastroesophageal cancer patients treated in high-volume hospitals have better outcomes [17][18][19][20][21][22][23][24][25]. Patient volume can therefore be regarded as a proxy for quality of care, possibly due to multimodal expertise and a well-developed organization of care in high-volume hospitals [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…During the present study interval, there was ongoing centralization of care, which is why the patient's county of residence was chosen as a yearly updated exposure. Other studies 29–31 of total resection rate, and especially the effect of centralization, in pancreatic and gastric cancer also reported associations between a higher total resection rate and survival benefit.…”
Section: Discussionmentioning
confidence: 86%